2017
DOI: 10.4103/jfo.jfds_64_15
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of antemortem dental records in private dental clinics: Knowledge, attitude, and practice among the practitioners of Mangalore and surrounding areas

Abstract: Introduction:With time, an increase in the number of crimes, mass disasters, and wars, has led to the identification of the deceased or assailant critical. In such circumstances, antemortem dental records play a crucial role.Materials and Methods:A cross-sectional survey involved 95 dentists practicing in and around Mangalore. The structured questionnaire comprised 24 questions regarding the practice of maintenance of dental records. The questionnaire was given either personally or sent by post. The data obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
3
2
1
Order By: Relevance
“…More than 80% of the participating dentists (n=130, 81.2%) were safe-keeping patient's radiograph either as hard or digital copy with themselves. This figure is higher than reported in dentists of Mangalore (59%) 12 , Punjab and Uttar Pradesh (47%) 9 , and Pune (77%) 11 .…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…More than 80% of the participating dentists (n=130, 81.2%) were safe-keeping patient's radiograph either as hard or digital copy with themselves. This figure is higher than reported in dentists of Mangalore (59%) 12 , Punjab and Uttar Pradesh (47%) 9 , and Pune (77%) 11 .…”
Section: Discussioncontrasting
confidence: 63%
“…In our study, only 46.2 % (n=74) of the participating dentists reported that they are keeping dental record digitally. This figure is higher than reported among dentists of Mangalore (2%) 12 , Pune (11%) 11 , Madhya Pradesh (24%) 17 and Rajasthan (26%) 10 . Dentists must be made aware of these soft wares.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Poor record keeping can be expected in less developed countries [ 16 , 18 , 22 , 23 , 24 ], but research shows such insufficiencies even in highly developed countries such as the United Kingdom, where as many as 44% inaccurate dental records were found [ 25 ]. Research in Sudan has shown that dental students keep dental records more accurately than dentists in private clinics [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Selain rekam medis kedokteran gigi, data ante mortem juga dapat berupa foto sewaktu masih hidup yang memperlihatkan gigi-geliginya. 36 Data post mortem mengacu pada data yang berhubungan dengan proses autopsi dan pemeriksaan pada jenazah. Tujuan autopsi adalah untuk mengetahui penyebab kematian, waktu kematian, cara kematian dan identitas jenazah.…”
Section: Discussionunclassified